Analisis Implementasi PSAK 216 pada Rumah Sakit Swasta : (Studi Kasus pada Rumah Sakit XYZ Surabaya) - Siburian, Batara Effenberg Abigael Marulitua; Widoretno, Astrini Aning (Jurnal Ekonomi Manajemen Akuntansi, 2025)
Hospitals are places that provide health services to the community through the services they offer. In their operations, hospitals require fixed assets to be us|ed ind|epe|nd|ently or i|n co|mbi|nati|on wi|th other assets in the hospital for long-term operations. The fixed assets us|ed by hospitals make a significant contribution because they require large expenditures and are used over the long term. This study was conducted with the aim of analyzing the application of fixed asset accounting treatment at XYZ Hospital in accordance with PSAK 216. This study adopted a descriptive qualitative methodological approach to achieve the predetermined research objectives. The data collection technique applied was conducting interviews with the asset management department and obtaining accounting treatment documents and a detailed list of fixed assets of XYZ Hospital. The research findings show that the handling of fixed assets and the implementation of PSAK 216 on fixed assets at XYZ Hospital indicate that XYZ Hospital records its fixed assets if they have a useful life of more than one year, measures the initial cost of assets from the acquisition price, revalues assets but there is no method explaining the calculation method, applies the straight-line method for depreciation, discontinues fixed assets if they can no longer be used, and records all these events in its financial statements. It is important to apply PSAK 216 in implementing accounting treatments to minimize and prevent the risk of fixed asset recording errors in financial statements.